МОНГОЛ УЛС ДАХЬ МОНГОЛ ГҮН УХААНЫ ТҮҮХИЙН СУДАЛГААНЫ ТУЛГАМДСАН АСУУДЛУУД: Р.Дарьхүү - Р.Дарьхүү, (Acta Mongolica, 2012)
In this paper, we aimed to consider urgent problems of contemporary research of the history Mongolian Philosophy in Mongolia. The reason is that research is the one of important part of the intellectual development of our nation. Deepening and widening of the research of the history Mongolian Philosophy and education is comprehensively significant in terms of scientific cognition and social and political aspects. A prominent scholar Jugder.Ch had valuably contributed to the study history of Mongolian philosophy. He had researched Mongolian traditional philosophy broadly from the very beginning to early period of the XX century. He studied peculiarities of development of philosophy of these periods respectively, and it his philosophy treatises it is explained that how Mongolians had developed unique philosophy. These treatises of Jugder. Ch are very important as they founded the research on development of Mongolian traditional philosophy well. Since 1990 the period Mongolian philosophy in democratic transformation is continuing. Now we research our rich heritages of Mongolian traditional philosophy, while enriching and using them for further transformation into contemporary thoughts and for creating national complex ideology of philosophy. On the other hand. Occidentalized tradition of socialist period has been kept and used in our society. Therefore we are responsible for introducing and inculcating our richness of heritage and inditional philosophy without any extrinsic influence and ideology of the world. Regarding this issue, doctor Dashpurev.D says in his paper 'That some intellectuals of Mongolians underestimate their raditional history and culture without having enough knowledge and exalt history and culture of others. It is clear that they are educated in foreign countn and overwhelmed with their culture.